Acute and chronic effects of aquatic treadmill training on land treadmill running kinematics: A cross-over and single-subject design approach - Bressel, Eadric; Louder, Talin J.; Hoover, James P.; Roberts, Luke C.; Dolny, Dennis G. (Journal of sports sciences, 2017)
The aim of this study was to determine if selected kinematic measures (foot strike index [SI], knee contact angle and overstride angle) were different between aquatic treadmill (ATM) and land treadmill (LTM) running, and to determine if these measures were altered during LTM running as a result of 6 weeks of ATM training. Acute effects were tested using 15 competitive distance runners who completed 1 session of running on each treadmill type at 5 different running speeds. Subsequently, three recreational runners completed 6 weeks of ATM training following a single-subject baseline, intervention and withdrawal experiment. Kinematic measures were quantified from digitisation of video. Regardless of speed, SI values during ATM running (61.3 ± 17%) were significantly greater (P = 0.002) than LTM running (42.7 ± 23%). Training on the ATM did not change (pre/post) the SI (26 ± 3.2/27 ± 3.1), knee contact angle (165 ± 0.3/164 ± 0.8) or overstride angle (89 ± 0.4/89 ± 0.1) during LTM running. Although SI values were different between acute ATM and LTM running, 6 weeks of ATM training did not appear to alter LTM running kinematics as evidenced by no change in kinematic values from baseline to post intervention assessments.